An Analysis of Students’ Perception toward Online Learning in Listening Class at English Department of UNP - Aditia, Aditia; Adnan, Aryuliva (Journal of English Language Teaching, 2024)
This research project aims to acquire insight into students' perspectives on online learning in listening classes at the English Department of UNP. The study population was all students enrolled in the English Education Program in the Department of English in 2021, with a sample size of 27 students from the K4 2021 class. The research instrument used was a questionnaire consisting of 52 questions in Google Forms format. The data analysis, conducted with SPSS 23 for Windows, showed that students' perceptions of online Basic listening learning scored an average of 78% in the Good category. The statistical significance of the test was below the significance level of 0.05, with a 5% degree of freedom.